EFEKTIFITAS SENAM HAMIL TERHADAP PENGURANGAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI BPM Bd LILIS SURYATI, S.ST CISARUA BOGOR - Puspitasari, Dewi; Saripah, Ai (Universitas Batam, 2020)
Back pain in pregnant women occurs due to a pain syndrome in the lower back region as a result of the influence of body gravity moving forward. The aim of this study was to determine the effectiveness of pregnancy exercise in reducing back pain in third trimester pregnant women at BPM Bd. L Cisarua Bogor in 2020. This study used experimental methods with pre and post experiment types with one group pre test and post test designs. The sample in this study were 7 people. Data were analyzed through the Wilcoxon Test. The results of the Wilcoxon test showed that there was a significant decrease between the mean pain intensity before and after being given pregnancy exercise where the Pvalue was 0.014, which means that there was a decrease in pain intensity in the third trimester of pregnant women after doing pregnancy exercise by 6 people (86%). It can be concluded that there is an effect of pregnancy exercise on the success of reducing back pain in third trimester pregnant women and there is no relationship between maternal age, knowledge, gestational age and parity on the reduction of back pain in third trimester pregnant women. It is hoped that all pregnant women should do routine pregnancy exercises to reduce the intensity of back pain in the third trimester of pregnancy.